Analisa Implementasi Total Productive Maintenance (TPM) Dan Usulan Perbaikan Menggunakan Metoda 5S Pada Lini Produk Giboult Joint (Studi Kasus : CV. Sispra Jaya Logam Pekanbaru) - Selera Sitepu; Anita Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This study aims to analyze the implementation of Total Productive Maintenance (TPM), as a case study of giboult joint product line in CV. Sispra Jaya Logam Pekanbaru. The TPM approach is used Overall Equipment Effectiveness (OEE) as a metric for defining machine/equipment effectiveness. In the research method is to collect OEE data and calculate the OEE value per giboult joint work cycle. Then analysis of six big losses, statistical analysis using SPSS 20 and proposed improvements using the 5S method. Production data of giboult joint product line was collected for the period of June 2017. From OEE value calculation analysis found that the value of OEE on giboult joint product line was still below world class (85%). From the analysis of six big losses and statistical tests it was known that the most significant effect on the low value of OEE on the giboult joint product line for the breakdown losses and reduced speed losses. The high reduced speed losses was caused by slow production process. And the high breakdown losses was caused by the lack of effectiveness of the work of the machine and operator. Proposed improvement using the 5S method to increase productivity and production quality in the company.Keywords : TPM, Method 5S, Overall Equipment Effectiveness (OEE), Six Big Losses, SPSS 20.